Meta-Analysis of the Effect of Heavy Lifting on Low Back Pain Among Health Workers - Khairunnisa; Tamtomo, Didik Gunawan; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Low back pain is common in healthcare workers including doctors, nurses, midwives and physiotherapists, due to the nature of their work. These healthcare workers are often involved in tasks that involve heavy lifting. Manual patient handling, and awkward postures that are an integral part of care may have an effect on musculoskeletal injuries. This study aims to analyze the effect of heavy lifting on low back pain among healthcare workers. Subjects and Method: This study is a systematic review and meta-analysis study. The search for articles was carried out in accordance with the PICO Model eligibility criteria which include: P = Health workers, I = Heavy lifting, C = No heavy lifting, O = Low back pain. The articles used came from 2 databases, namely: PubMed and Science Direct. The keywords used were